2011
DOI: 10.1177/0040517511424528
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the spinnability of metallocene cyclic olefins copolymer melt

Abstract: This work investigates the melt spinning process of the metallocene cyclic olefins copolymer (mCOC), which had never been successfully developed before. The shear-viscosity examination reveals that the mCOC has a mild shear thinning tendency due to the presence of cyclic olefins, but is very sensitive to the temperature variation. The optimal melt extrusion temperature for the mCOC is found between 320 and 330°C. The mCOC is known to have high Tg, which would cause early solidification, seriously broken filame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Table 2 demonstrates that the tilt displacement can be reduced from approximately 4 mm to zero regardless of the compositions of the laminates as the setting temperature is increased to 120 C. Notably, the effective setting temperature, 120 C, is far from the T g values of the epoxy (227 C) and mCOC fabrics (187 C). Our previous study 14 found that micro crystals of the olefin (PE) block appeared among the cyclic groups inside the mCOC chains. Setting at 120 C under compression can soften and reshape the micro crystallized PE domains of mCOC fabrics, relaxing the residual stress at the glass/mCOC interface of the prepregs inside the composite.…”
Section: Characterization Of CCL Compositementioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 demonstrates that the tilt displacement can be reduced from approximately 4 mm to zero regardless of the compositions of the laminates as the setting temperature is increased to 120 C. Notably, the effective setting temperature, 120 C, is far from the T g values of the epoxy (227 C) and mCOC fabrics (187 C). Our previous study 14 found that micro crystals of the olefin (PE) block appeared among the cyclic groups inside the mCOC chains. Setting at 120 C under compression can soften and reshape the micro crystallized PE domains of mCOC fabrics, relaxing the residual stress at the glass/mCOC interface of the prepregs inside the composite.…”
Section: Characterization Of CCL Compositementioning
confidence: 99%
“…mCOC fabric mCOC fiber was formed via the melt-spinning process that is described in the authors' previous study. 14 The spinneret that was used in this experiment had 48 holes, each with a diameter of 0.2 mm, to produce the filaments with a yarn fineness of 150 d/48 f. Notably, the stiff surface of the mCOC fiber caused a serious peeling problem, which interrupted the weaving process. Wrapping the as-spun mCOC yarns with a PVA bundle to form a ''PVA/mCOC single cover yarn'' (Figures 1(a) and (b)) was found to be an effective means of making a plain-weaved mCOC fabric.…”
Section: Materials Of Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also been made in other fields, concerning the formation of COC nanoparticles [35], production of COC/silica nanocomposites foams [36] and the processability of COC yarn by melt spinning [37]. Very recently, a paper has been published by Saadé et al [38], concerning the modification of cyclic olefin copolymer in order to conduct to new electrochromatographic stationary phases.…”
Section: Introductionmentioning
confidence: 99%
“…If the drawing temperature is too low or too high, the mechanical property of fibers is decreased accordingly. [21][22][23] The degree of orientation of fibers can be determined by birefringence, sonic modulus or X-ray diffraction methods where the birefringence method measures the orientation of the segment of molecular chains, the sonic modulus method measures the bulk-orientation of fibers and the X-ray diffraction method measures the orientation of the crystalline region. [24][25][26] In this study, as-spun fibers were fabricated by melt spinning 1 using EVOH raw materials with various ethylene contents (EV-32, EV-38 and EV-44 roughly having 32, 38 and 44 mole% of ethylene composition units, respectively) to search for the optimal drawing temperature.…”
mentioning
confidence: 99%